Suppose i have a formal power series

$$f(t)=e^t-1-t=\sum_{k=2}^\infty \frac{t^k}{k!}$$

How would I go about finding its compositional inverse? Trying to find the inverse of $f(t)=e^t-1-t$ i think is impossible to solve for $t$ w/o using like the Lambert W-function. However, is there a way to find it using power series? Perhaps there is a way to extract the coefficients then...

  • $\begingroup$ Do you mean that you want to find the power series of the inverse for $e^t -t -1$? Or did you mean in general for any analytic function? $\endgroup$ – Qudit Nov 15 '17 at 0:21
  • $\begingroup$ For the inverse of $e^t-1-t$ $\endgroup$ – AveryJessup Nov 15 '17 at 0:22
  • 3
    $\begingroup$ The compositional inverse of a formal power series can be found using what is known as the Lagrange inversion theorem. $\endgroup$ – omegadot Nov 15 '17 at 1:14
  • $\begingroup$ "However, is there a way to find it using power series?" - this amounts to directly finding the series expansion of the Lambert-based function in fact. $\endgroup$ – J. M. is a poor mathematician Nov 15 '17 at 2:59
  • 1
    $\begingroup$ @Markus Scheuer: Yes, you are right. In this particular case a compositional inverse does not exist. $\endgroup$ – omegadot Nov 16 '17 at 9:52

Given $f(x):=e^x-1-x,$ let $\;g(x) := x - 1/6 x^2 + 1/36 x^3 - 1/270 x^4 + 1/4320 x^5 + O(x^6).\;$ The function $\;\sqrt{2f(x)}=x + 1/6 x^2 + 1/36 x^3 + 1/270 x^4 + 1/2592 x^5 + O(x^6)\;$ is its inverse. Thus $h(x):=g(\sqrt{2x}) = \sqrt{2x} - 1/3x + 1/18\sqrt{2x}x -2/135x^2 + O(x^{5/2})\;$ is the Puiseux series inverse of $f(x).\;$ Solve for the coefficients of $\;g(x),\;$ and hence $h(x),\;$ one at a time using either one of the equations $\;f(g(x))=x^2/2\;$ or $\;g(\sqrt{2f(x)})=x.$

  • $\begingroup$ As I can see, you already found the relationship with Puiseux series. :-) $\endgroup$ – Markus Scheuer Nov 16 '17 at 11:57

A compositional inverse $g(t)$ of the function $f(t)$ fulfilling $$f(g(t))=t=g(f(t))$$does not exist in the ring of formal power series.

We find in section 5.4 The Lagrange Inversion Formula of Enumerative Combinatorics 2 by R.P. Stanley:

  • The set $xK[[x]]$ of all formal power series $a_1x+a_2x^2+\cdots$ with zero constant term over a field $K$ forms a monoid under the operation of functional composition. The identity element of this monoid is the power series $x$.

    Recall ... that if $f(x)=a_1x+a_2x^2+\cdots\in K[[x]]$, then we call a power series $g(x)$ a compositional inverse of $f$ if $f(g(x))=g(f(x))=x$, in which case we write $g(x)=f^{\langle-1\rangle}(x)$. The following simple proposition explains when $f(x)$ has a compositional inverse.

  • Proposition 5.4.1 A power series $f(x)=a_1x+a_2x^2+\cdots\in K[[x]]$ has a compositional inverse $f^{\langle-1\rangle}$ if and only if $a_1\ne 0$, in which case $f^{\langle -1\rangle}(x)$ is unique. Moreover, if $g(x)=b_1x+b_2x^2+\cdots$ satisfies either $f(g(x))=x$ or $g(f(x))=x$, then $g(x)=f^{\langle-1\rangle}(x)$.

    Proof. Assume that $g(x)=b_1x+b_2x^2+b_3x^3+\cdots$ satisfies $f(g(x))=x$. We then have

    \begin{align*} \color{blue}{a_1(b_1x}+b_2x^2+b_3x^3+\cdots) +a_2(b_1x+b_2x^2+\cdots)^2+a_3(b_1x+\cdots)^3+\cdots\color{blue}{=x} \end{align*} Equating coefficients on both sides yields the infinite system of equations \begin{align*} \color{blue}{a_1b_1}&\color{blue}{=1}\\ a_1b_2+a_2b_1^2&=0\\ a_1b_3+2a_2b_1b_2+a_3b_1^3&=0\\ &\vdots\\ \end{align*} We can solve the first equation (uniquely) for $b_1$ if and only if $a_1\ne 0$.

Since $a_1=[t^1]f(t)=[t^1](e^t-1-t)=0$ we conclude $f(t)$ has no compositional inverse in the ring of formal power series.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.